Should We Re-think Regulations and Standards for Lighting at Workplaces? A Practice Review on Existing Lighting Recommendations - Stefani, Oliver; Cajochen, Christian (Frontiers in Psychiatry, 2021)
Nowadays lighting projects often include temporal variations of the light, both spectrally and in terms of intensity to consider non-visual effects of light on people. However, as of today there are no specific regulations. Compliance with common lighting standards that address visual aspects of light, often means that only little non-visually effective light reaches the eye. In this practice review we confront existing regulations and standards on visual lighting aspects with new recommendations on non-visual aspects and highlight conflicts among them. We conclude with lighting recommendations that address both aspects.